2016
DOI: 10.3390/toxins8020053
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the Mode of Action of Haedoxan A from Phryma leptostachya

Abstract: Haedoxan A (HA) is a major active ingredient in the herbaceous perennial plant lopseed (Phryma leptostachya L.), which is used as a natural insecticide against insect pests in East Asia. Here, we report that HA delayed the decay rate of evoked excitatory junctional potentials (EJPs) and increased the frequency of miniature EJPs (mEJPs) on the Drosophila neuromuscular junction. HA also caused a significant hyperpolarizing shift of the voltage dependence of fast inactivation of insect sodium channels expressed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 45 publications
2
18
0
Order By: Relevance
“…3B-II and 3C-II). Consistent with the observations reported for cockroach sodium channels expressed in oocytes (Hu et al, 2016), we found that HA did not modify the voltage-dependent activation or recovery from fast and slow inactivation of either the wild-type DmNa v 22 or I265N mutant channels (Fig. 3A-II, 3D-II, and 3E-II).…”
Section: I265n Mutation Abolished the Ha-induced Hyperpolarizing Shif...supporting
confidence: 92%
See 2 more Smart Citations
“…3B-II and 3C-II). Consistent with the observations reported for cockroach sodium channels expressed in oocytes (Hu et al, 2016), we found that HA did not modify the voltage-dependent activation or recovery from fast and slow inactivation of either the wild-type DmNa v 22 or I265N mutant channels (Fig. 3A-II, 3D-II, and 3E-II).…”
Section: I265n Mutation Abolished the Ha-induced Hyperpolarizing Shif...supporting
confidence: 92%
“…Subsequently, we evaluated the effects of HA on DmNa v 22 channel function, and consistent with the results obtained in previous studies on cockroach sodium channels expressed in oocytes (Hu et al, 2016), we found that at a concentration of 3 μmol/L, HA induced hyperpolarizing shifts in the voltage dependence of both the fast and slow inactivation of DmNa v 22 channels . The voltage dependences of fast and slow inactivation were significantly shifted by 7.2 mV and 2.9 mV, respectively, in the hyperpolarizing direction.…”
Section: I265n Mutation Abolished the Ha-induced Hyperpolarizing Shif...supporting
confidence: 85%
See 1 more Smart Citation
“…Haedoxans exhibit excellent insecticidal activity against several insects, such as Musca domestica [Culex pipiens pallens (Xiao et al, 2012b)] and Mythimna separata (Xiao et al, 2012a). It is noteworthy that the insecticidal activity of Haedoxan A (1) is comparable to that of the commercial synthetic pyrethroids (Taniguchi et al, 1989;Hu et al, 2016). (+)-Phrymarolins I (4) and II (5) also show considerable synergistic activities with pyrethrin and carbamate pesticides (Park et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…These lignans from P. leptostachya exhibited highly efficient insecticidal activities against a variety of pests [6,15,16], which aroused our interest. For example, haedoxan A displayed remarkably high insecticidal activity against the housefly, which was approximate with common synthetic pyrethroids [17,18,19,20].…”
Section: Introductionmentioning
confidence: 99%